2011
DOI: 10.2989/10220119.2011.571402
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of seed dispersal and establishment of the invaderProsopis juliflorain the upper floodplain of Tana River, Kenya

Abstract: Invasive species in Africa have important impacts on food security and biodiversity conservation. African floodplains in arid areas are critical wildlife habitats in addition to crop production and dry season livestock grazing. The study aimed to understand the patterns of spread of the invader Prosopis juliflora in a typical African floodplain characterised by both multiple dispersers and habitats. Data was collected on faecal seed density, establishment and vegetation composition, and subjected to non-parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…Approximately, 40 species (trees and shrubs) are native to North and South America (Pasiecznik et al, 2001). However, they have been introduced and have adapted to dry lands of Asia, Africa and Australia because of their commercial value, contribution to land rehabilitation, and provision of fodder and firewood (Mwangi & Swallow, 2008;Mworia et al, 2011). Mesquite pods (referred to henceforth as fruits) vary in colour from white to red and dark brown.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately, 40 species (trees and shrubs) are native to North and South America (Pasiecznik et al, 2001). However, they have been introduced and have adapted to dry lands of Asia, Africa and Australia because of their commercial value, contribution to land rehabilitation, and provision of fodder and firewood (Mwangi & Swallow, 2008;Mworia et al, 2011). Mesquite pods (referred to henceforth as fruits) vary in colour from white to red and dark brown.…”
Section: Introductionmentioning
confidence: 99%
“…Provision of wood fuel was one of the main objectives of Prosopis species introduction in the country (Mwangi and Swallow, 2008). This objective is not yet fully realized, despite the successful establishment of the species in the initial trials (Maghembe et al, 1983;Olukoye et al, 2003) and their subsequent spread into other unintended areas, as a result of natural seed dispersal by livestock, wild animals and water (Mwangi and Swallow, 2008;Mworia et al, 2011). Recently, the government gave a policy direction for utilization of Prosopis species to control their further spread in areas where they are invasive (GOK, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Propagule pressure across habitats in an ecosystem can be enhanced if the invasive species has multiple dispersal agents. For example Mworia et al (2011) observed that the invader Prosopis juliflora was dispersed by several wildlife and livestock species within the savanna of the upper Tana River floodplain resulting in a significant association between habitat type and disperser type indicating the importance of habitat preference and livestock herding patterns. Characteristics of non-native species can be an indicator of its potential invasiveness in the new community.…”
Section: Factors That Enhance Invasibility In Savannasmentioning
confidence: 99%
“…It is important to note that disturbances create opportunities for both natives and non-natives and for the prevalence of non-natives to increase there must a source of non-native propagule (Lockwod et al, 2007). Lets again take the example of the Prosopis juliflora in savanna floodplain of upper Tana River in Kenya where Mworia et al (2011) found that ecological disturbance manifested by rested crop fields not only enhanced the establishment of the invader but also had a positive effect on indigenous woody species. Rested crop fields have vegetation and soil disturbance and represent early stages of plant succession.…”
Section: Factors That Enhance Invasibility In Savannasmentioning
confidence: 99%